Linking compliance and policy learning - Thenia Vagionaki (International Review of Public Policy)
This article analyzes the link between compliance and policy learning. It argues that member states that tend to comply with EU regulations are also more prone to learn from EU soft law instruments, such as the Open Method of Co-ordination (OMC). To empirically demonstrate this argument, the article offers evidence from two illustrative case studies, Greece and Spain, based on insights from semi-structured interviews conducted with EU and national experts. The evidence shows that in Greece, compliance is problematic and learning – via EU soft law – remains mostly blocked. In Spain, where compliance is stronger, learning is more instrumental and political in nature. By focusing on the critical period before and right after the 2008 financial crisis, the article explains the different trajectories of these two Southern European countries with respect to their EU obligations through the lens of policy learning.